Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/1750-3841.12920
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sausages Containing Mechanically Deboned Chicken Meat Hydrolysates

Abstract: In most of the developed countries, meat from spent laying hens is not consumed, leading toan urgent need for effectively utilization or disposal methods. In this study, sausages were prepared using spent laying hens and protein hydrolysates from mechanically deboned chicken meat. Sausage can be made by spent laying hens hydrolysates, although overall acceptability was lower than those of other sausage samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
6
10
0
Order By: Relevance
“…However, a* value was higher in treated samples than control throughout the storage period and rate of decrease in a* value was significantly (P \ 0.05) lower in treated products than control. Similar results were reported by Jin et al (2015) for meat sausages on the addition of mechanically deboned chicken meat hydrolysates, the redness (a*) values of product remained significantly (P \ 0.05) higher than control, before and after storage. This indicated that incorporation of the blood protein hydrolysate might be effective in controlling chemical rancidity as well as red colour deterioration.…”
Section: Colour Parametersupporting
confidence: 87%
“…However, a* value was higher in treated samples than control throughout the storage period and rate of decrease in a* value was significantly (P \ 0.05) lower in treated products than control. Similar results were reported by Jin et al (2015) for meat sausages on the addition of mechanically deboned chicken meat hydrolysates, the redness (a*) values of product remained significantly (P \ 0.05) higher than control, before and after storage. This indicated that incorporation of the blood protein hydrolysate might be effective in controlling chemical rancidity as well as red colour deterioration.…”
Section: Colour Parametersupporting
confidence: 87%
“…CPE could reduce methemoglobin accumulation by inhibiting lipid oxidation, thereby protecting the patties from discoloration (Faustman, Sun, Mancini, & Suman, 2010). Our results are consistent with those of Jin et al (2015).…”
Section: Resultssupporting
confidence: 94%
“…However, treated emulsions had higher ES and moisture content as compared to the control. Similar observations were also reported by Jin et al (2015) and Vioque et al (2000), which might be due to improved water holding capacity and emulsifying properties of protein hydrolysates. Further, the concept was generated that exposed hydrophobic amino acid residues in proteins hydrolysates would also contribute to the improvement of emulsions.…”
Section: Physico-chemical Properties Of Emulsion and Cooked Chevon Pattiessupporting
confidence: 88%
“…Notes: Mean values bearing different superscripts in a row differ significantly ( p Ͻ 0.05) n ϭ 6; statistical tests used: one-way ANOVA; C ϭ control (chevon patties without protein hydrolysate); T 1 ϭ chevon patties with 0.09% CMPH-A; T 2 ϭ chevon patties with 0.06% CMPH-C; T 3 ϭ chevon patties with 0.09% CMPH-P NFS 47,2 physico-chemical (CY, a w , per cent protein, per cent fat, per cent ash and per cent dietary fibre) as well as dimensional (per cent gain in height and decrease in diameter) parameters were comparable amongst treatments and the control. Similar observations were also reported in sausage containing mechanically deboned chicken meat hydrolysates ( Jin et al, 2015). The pH values of treated cooked patties differ significantly ( p Ͻ 0.05), and the lowest value was recorded for T 3 , whereas it was comparable in other treatments.…”
Section: Physico-chemical Properties Of Emulsion and Cooked Chevon Pattiessupporting
confidence: 85%